State centric versus human centric: how should water as a conflict variable be understood? - De Sao Joao, Ricardo (My University, 2013)
In this thesis, the continuous dialogue between state-centered and human-centered approaches to security studies is discussed in the context of their ability to explain emerging threats within the international system. One emerging threat that has received a particularly large amount of attention is the possibility of water wars in the future. Water Wars are deemed to be conflicts that have water as their primary driving force, both in the onset and continuation. Through the use of the Chad River Basin and the Nile River Basin, this thesis will determine how each approach to security studies explains a particular conflict over water by, considering how each of them explain a “water war” within these Basins. Importantly, through this approach, the thesis aims to determine in what way, if any, the human- centered approach offers a better explanation to water-related conflict than state-centered security. In doing so, the thesis unpacks the various factors relating to the use, distribution and management of shared watercourses. While the findings in this thesis are not exhaustive, it is hoped that it will provide insight into how one ought to understand who is likely to be party to water wars and what is likely to be threatened in these water wars.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, International Relations, 2013